Overdensity of galaxies in the environment of quasar pairs. Issue 4 (31st October 2017) - Sandrinelli, A; Falomo, R; Treves, A; Scarpa, R; Uslenghi, M
Abstract: We report on a study of the galaxy environments of low redshift physical quasars pairs. We selected 20 pairs having projected separation < 0.5 Mpc and difference of systemic velocity < 800 km s −1 . Using Sloan Digital Sky Survey images, we evaluated the galaxy overdensity around these quasars in pairs and then compare it with that of a sample of isolated quasars with same redshift and luminosity. It is found that on average there is a systematic larger overdensity of galaxies around quasars in pairs with respect to that of isolated quasars. This may represent a significant link between nuclear activity and galaxy environment. However, at odds with that, the closest quasar pairs seem to inhabit poorer environments. Implications of present results and perspectives for future work are briefly discussed.